1994
DOI: 10.1007/bf02815353
|View full text |Cite
|
Sign up to set email alerts
|

Neutral glycolipid composition of primary human brain tumors

Abstract: Neutral glycolipids (NGL) were isolated and quantitated in 98 primary human brain tumors; 19 low grade astrocytomas (LGA), 12 anaplastic astrocytomas (AA), 37 high grade astrocytomas (HGA), 18 oligodendroglial tumors, and 12 primitive neuroectodermal tumors (PNET). In 38 of these, the nature of the hexose in the cerebroside was determined using immunothin-layer chromatographic techniques. Galactosylceramide (GalCer) was the major ceramide monohexoside (CMH), and glucosylcerebroside never comprised more than 6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The higher PC/PE ratio in NF1T cells compared to that in PNS myelin may indicate changes in membrane fluidity associated with malignancy (Schroeder, 1980). The lower content of cerebrosides and sulfatides compared to CNS myelin (Kirschner et al, 1989) may be related to the lack of differentiation and to the tumorigenic character of the NF1T cells (Chen et al, 1989;Sinagh et al, 1994). 0.37 6 0.03 24.6 6 1.4 10.0 6 0.7 15.0 6 1.1 PI 0.33 6 0.02 12.5 6 0.5 8.6 6 0.5 31.1 6 2.1 PS 0.014 6 0.001 3.9 6 0.2 9.8 6 0.55 3.6 6 0.15 *A 5 % of each phospholipid (with respect to the total content of its own class in the plasma membrane) at the outer leaflet of the PM, and was calculated with the following computational procedure: A 5 (H 3 100/a) (100/b), where H 5 % of phospholipid class degraded in non-lytic conditions with respect to total cellular phospholipids (data taken from Figure 3); a 5 % phospholipid class with respect to total cellular phospholipid (data taken from Table II, column 1); b 5 % PM phospholipid class with respect to total cellular phospholipid.…”
Section: Discussionmentioning
confidence: 99%
“…The higher PC/PE ratio in NF1T cells compared to that in PNS myelin may indicate changes in membrane fluidity associated with malignancy (Schroeder, 1980). The lower content of cerebrosides and sulfatides compared to CNS myelin (Kirschner et al, 1989) may be related to the lack of differentiation and to the tumorigenic character of the NF1T cells (Chen et al, 1989;Sinagh et al, 1994). 0.37 6 0.03 24.6 6 1.4 10.0 6 0.7 15.0 6 1.1 PI 0.33 6 0.02 12.5 6 0.5 8.6 6 0.5 31.1 6 2.1 PS 0.014 6 0.001 3.9 6 0.2 9.8 6 0.55 3.6 6 0.15 *A 5 % of each phospholipid (with respect to the total content of its own class in the plasma membrane) at the outer leaflet of the PM, and was calculated with the following computational procedure: A 5 (H 3 100/a) (100/b), where H 5 % of phospholipid class degraded in non-lytic conditions with respect to total cellular phospholipids (data taken from Figure 3); a 5 % phospholipid class with respect to total cellular phospholipid (data taken from Table II, column 1); b 5 % PM phospholipid class with respect to total cellular phospholipid.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports that such tumors frequently express sulfatide and/or GalC (Jennemann et al, 1990;Singh et al 1994), and that some glioma-derived cell lines can be induced to express GalC or mRNA for proteolipid protein (Gillaspy et al, 1993;Kashima et al, 1993), are consistent with the view that the Hu-O-2A/Gb1 cell line is not a unique example of an O-2A tumour.…”
Section: Discussionmentioning
confidence: 57%
“…0 1 is a reliable indicator of surface galactosylcerebroside (Bansal et a]., 1989), but 0 1 also reacts with an unidentified antigen in rat brain extracts . In view of this it is important to note that we have found considerable amounts of chemically characterized galactosylcerebroside in human primary brain tumors (Singh et al, 1991(Singh et al, , 1994. It might be thought that some of this could be in residual myelin of brain infiltrated by the tumor.…”
Section: Immunostaining Of Non-neoplastic Brain Tissues Discussionmentioning
confidence: 83%
“…In a recent biochemical study we found that there were considerable amounts of galactosylcerebroside, sulfatide, and other neutral glycolipids in several types of primary human brain tumors (Singh et al, 1994). It was interpreted that these glycolipids were an integral component of the tumor cells.…”
Section: Double Immunofluorescent Stainingmentioning
confidence: 96%